PEMBERIAN PENGUATAN OLEH GURU IPS TERPADU DALAM MENINGKATKAN MOTIVASI BELAJAR SOSIOLOGI - Obertus, Obertus; Astriati, Nuraini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis writing aims to determine the understanding of the provision of reinforcement, both verbal and non verbal in increasing student motivation to study the soliology of IPS-Integrated subjects in class IX. This research is a qualitative descriptive study. The informants in this study were IPS-Integrated teachers and class IX students, secondary data sources were obtained from documentation and archives relating to research. Data collection technique is an observation technique with observation guide data collection tools, interview guides and archives. Observation activities were carried out twice, the interview with the teacher was conducted carried one twice dan iInterviews with students were conducted three twice. The results of this study indicate that 1) The provision of verbal reinforcement by IPS-Integrated teachers in increasing the motivation of learning Sociology in class IX students of SMP Negeri 8 Tanah Pinoh District Melawi Regency, which included words of praise, words of advice and polite and gentle language have been carried out by IPS-Integrated teachers. 2) Giving non-verbal reinforcement by Integrated Social Sciences teachers in increasing Sociology learning motivation in class IX students of SMP Negeri 8 Tanah Pinoh Subdistrict Melawi District which includes strengthening gestures, approaching and strengthening in the form of signs or objects, has been done by the teacher IPS-Integrated.Â Keywords: Strengthening, Learning Motivation, Social Studies Teacher